A law regulating taxation of pension benefits in South Africa - Segodi, Vusi Oscar (University of Limpopo, 2015)
This mini-dissertation discusses the legal reform of the taxation of pension benefits under the South African law. This study also discusses how South African pension benefits are taxed in instances wherein the member exits the fund either as a result of resignation, death, dismissal, retrenchment, disability and retirement. It further discusses the comparative study between South Africa, Canada, Australia and United Kingdom
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2015
Keywords: Taxation; Pension benefits; South African law; Postemployment benefits; Defined benefit pension plans -- Law and legislation